A catalytic cracking catalyst and its preparation method
By supporting the nitrogen-trapping active components such as oxides of metal zirconium in the catalyst, the toxicity problem of high nitrogen-containing raw materials to the catalyst is solved, and the resistance to alkali nitrogen poisoning and product quality of the catalytic cracking catalyst is improved.
Patent Information
- Application Number
- CN202010433083.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-05-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-05-20
AI Technical Summary
During the fluidized catalytic cracking process, high nitrogen-containing raw materials lead to a decrease in catalyst activity, weakening of selectivity, and deterioration of product distribution. The existing nitrogen removal process is costly or inefficient, making it difficult to apply on a large scale.
Design a catalyst to selectively adsorb nitrogen-containing compounds by supporting the trapping of nitrogen-containing active components, such as oxides of metal zirconium, promote their cracking and condensation and dehydrogenation reactions, avoid nitrogen-containing compounds from entering the product, and improve the catalyst's alkali-resistant nitrogen Poisoning ability.
It improves the resistance to alkali nitrogen poisoning of catalytic cracking catalysts, improves the conversion rate and product quality of high nitrogen-containing raw materials, reduces the nitrogen content in the target products, and is suitable for catalytic cracking of hydrocarbon oils with high alkali nitrogen content.
Smart Images

Figure BDA0002499655660000051 
Figure BDA0002499655660000101 
Figure BDA0002499655660000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of petroleum processing, and relates to a catalytic cracking catalyst, in particular to a catalytic cracking catalyst with high resistance to alkali nitrogen poisoning and a preparation method thereof. Background Art
[0002] Fluidized catalytic cracking (FCC) is one of the most important processes for lightening heavy oil in the petroleum refining industry. It is responsible for producing light oil products (gasoline, diesel, etc.) and chemical raw materials (ethylene, propylene, butene, etc.) using heavy oil (vacuum wax oil, residual oil, etc.) as raw materials. In recent years, with the tight supply of conventional oil and the continuous increase in consumer demand, crude oil prices have remained high, and the trend of crude oil degradation and heaviness has continued to intensify. Blending or directly processing low-quality raw materials such as residual oil and coker gas oil (CGO) in FCC units to the greatest extent has become an important way for oil refineries to expand FCC raw material sources and tap potential and increase efficiency. Compared with the conventional FCC raw material - straight run gas oil (VGO), the outstanding characteristics of these low-quality raw materials are high density, high viscosity, high content of heteroatoms such as heavy metals, sulfur, and nitrogen, high content of colloidal asphaltene, and poor cracking ability. FCC catalysts are required to have not only good heavy oil cracking ability, but also multiple functions such as resistance to metal, sulfur, and nitrogen pollution and residual carbon conversion. With the increasing amount of inferior raw materials such as residual oil and CGO, the nitrogen-containing compounds in FCC raw materials increase accordingly. Due to the toxic effect of nitrogen-containing compounds on catalysts, it is bound to lead to a decrease in catalyst activity and selectivity, a decrease in the single-pass conversion rate of raw materials, an increase in the amount of recycled oil and external slurry, an increase in coke yield, a deterioration in product distribution, and a decrease in product quality.
[0003] At present, the measures to inhibit or eliminate the adverse effects of nitrogen-containing compounds on the FCC process mainly include two aspects. One is to carry out raw material pretreatment processes such as hydrodenitrogenation, complex denitrogenation, adsorption denitrogenation, solvent extraction denitrogenation and acid neutralization denitrogenation for FCC raw materials. The other is to adopt nitrogen-resistant catalytic cracking processes and use nitrogen-resistant catalysts or additives. Among these measures, raw material hydrodenitrogenation is considered to be the most effective method. However, due to the high investment and operating costs of hydrogenation units, especially in the context of my country's very limited hydrogenation capacity, the large-scale application of FCC raw material hydrodenitrogenation process in industry is seriously affected. Other raw material denitrogenation processes have the disadvantages of low denitrogenation rate, low oil yield after denitrogenation, difficult denitrogenation agent recovery, and high denitrogenation cost, and there are few reports on industrial applications. Therefore, it is currently considered to be a relatively economical and effective way to improve the ability of FCC units to process high-nitrogen raw materials by improving the FCC process or using nitrogen-resistant catalysts and additives.
[0004] Strong adsorption and preferential adsorption of nitrogen-containing compounds are key factors causing catalyst poisoning. Therefore, a special active material can be designed to have a strong adsorption capacity for nitrogen-containing compounds (referred to as nitrogen-capturing active component in the present invention), and then this nitrogen-capturing active component can be loaded on the carrier surface of the catalyst to selectively adsorb nitrogen-containing compounds. This can avoid the poisoning effect of nitrogen-containing compounds on ordinary molecular sieves used for hydrocarbon cracking, and make hydrocarbon molecules and nitrogen-containing compound molecules in heavy oil "react separately". At the same time, this special active material can also promote the cracking reaction of nitrogen-containing compounds, especially condensation dehydrogenation reaction. Through the transfer of hydrogen, the nitrogen-containing compounds are highly condensed. On the one hand, hydrogen is effectively transferred to the target product, the utilization rate of hydrogen in the raw material is improved, and the product quality is improved. On the other hand, nitrogen is adsorbed on the catalyst and removed in the form of coke to avoid nitrogen-containing compounds from entering the target product, thereby reducing the adverse effects of nitrogen-containing compounds on the properties of the target product and subsequent processing.
[0005] Patent CN103084200A discloses an alkali-nitrogen-resistant catalytic cracking catalyst and a preparation method thereof, wherein the catalyst comprises a cracking active component, clay and a binder, and contains or does not contain a mesoporous silica-alumina material; wherein the cracking active component comprises a Y-type molecular sieve modified with rare earth, iron, copper and phosphorus, wherein the rare earth content in the molecular sieve is 8-23 wt% in terms of rare earth oxide, the iron content is 0.1-3.0 wt% in terms of Fe2O3, the copper content is 0-3.0 wt% in terms of CuO, the phosphorus content is 0-2.0 wt% in terms of P2O5, and the sodium oxide content is 0.1-2.5 wt%. The preparation method comprises mixing and slurrying the cracking active component, the mesoporous silica-alumina material, clay and the binder, and then spray drying, washing, filtering and drying in sequence, wherein the catalyst is used for catalytic cracking of hydrocarbon oil with a higher alkali nitrogen content and has a higher activity.
[0006] Patent CN103084199A discloses a alkali-resistant nitrogen-reducing olefin cracking catalyst and a preparation method thereof, wherein the catalyst comprises a cracking active component, a mesoporous silicon-aluminum material, a binder and clay, wherein the cracking active component comprises a first Y-type molecular sieve and a second Y-type molecular sieve, wherein the rare earth content in the first Y-type molecular sieve is 8-23% by weight in terms of rare earth oxide, the iron content is 0.1-3.0% by weight in terms of Fe2O3, the copper content is 0-3.0% by weight in terms of CuO, the phosphorus content is 0-2.0% by weight in terms of P2O5, and the sodium oxide content is 0.1-2.5% by weight; the second Y-type molecular sieve is a phosphorus and rare earth modified Y-type molecular sieve. The preparation method of the catalyst comprises the steps of preparing a slurry comprising a cracking active component, a mesoporous silicon-aluminum material, a binder and clay, spray drying, washing and drying. The catalyst is used for catalytic cracking of hydrocarbon oils with a higher alkali nitrogen content, and has a higher conversion rate and a lower gasoline olefin content.
[0007] Patent CN103084205A discloses a cracking catalyst resistant to alkali nitrogen and high-yield liquefied gas and its preparation method, wherein the catalyst comprises a cracking active component, a mesoporous silicon-aluminum material, a binder and clay, wherein the cracking active component comprises a Y-type molecular sieve and an MFI structure molecular sieve, and the Y-type molecular sieve comprises a rare earth content of 8-23% by weight in terms of rare earth oxide, an iron content of 0.1-3.0% by weight in terms of Fe2O3, a copper content of 0-3.0% by weight in terms of CuO, a phosphorus content of 0-2.0% by weight in terms of P2O5, and a sodium oxide content of 0.1-2.5% by weight. The preparation method of the catalyst comprises the steps of beating the cracking active component, the mesoporous silicon-aluminum material, the clay and the binder, spray drying, washing, filtering and drying. The catalyst is used for catalytic cracking of alkali-nitrogen-containing feedstock oil, and has a high conversion rate and a high liquefied gas yield.
[0008] Patent CN103084206A discloses a catalytic cracking catalyst with high alkali nitrogen resistance and diesel production and a preparation method thereof, wherein the catalyst comprises a cracking active component, a mesoporous silicon-aluminum material, a binder and clay, wherein the cracking active component comprises a first Y-type molecular sieve and a second Y-type molecular sieve, with or without a third Y-type molecular sieve, wherein the rare earth content in the first molecular sieve is 8-23% by weight in terms of rare earth oxide, the iron content is 0.1-3.0% by weight in terms of Fe2O3, the copper content is 0-3.0% by weight in terms of CuO, the phosphorus content is 0-2.0% by weight in terms of P2O5, and the sodium oxide content is 0.1-2.5% by weight; the second Y-type molecular sieve is an ultra-stable Y-type molecular sieve containing magnesium, and the third Y-type molecular sieve is a DASY molecular sieve containing rare earth. The preparation method of the catalyst comprises the steps of slurrying the cracking active component, the mesoporous silicon-aluminum material, the clay and the binder, spray drying, washing, filtering and drying. The catalyst is used for catalytic cracking of hydrocarbon oil with a higher basic nitrogen content and has a higher conversion rate and diesel yield.
[0009] Patent CN103084207A discloses a catalytic cracking catalyst with high gasoline production and a preparation method thereof, wherein the catalyst comprises a cracking active component, a mesoporous silicon-aluminum material, a binder and clay, wherein the cracking active component comprises a first Y-type molecular sieve and an ultra-stable Y-type molecular sieve containing rare earths, wherein the rare earth content in the first Y-type molecular sieve is 8-23% by weight in terms of rare earth oxide, the iron content is 0.1-3.0% by weight in terms of Fe2O3, the copper content is 0-3.0% by weight in terms of CuO, the phosphorus content is 0-2.0% by weight in terms of P2O5, and the sodium oxide content is 0.1-2.5% by weight. The preparation method of the catalyst comprises the steps of slurrying the cracking active component, the mesoporous silicon-aluminum material, the clay and the binder, spray drying, washing, filtering and drying. The catalyst is used for catalytic cracking of hydrocarbon oil with high alkali nitrogen content, and has a higher conversion rate and gasoline yield.
[0010] The above patent adopts a similar method to modify the Y-type molecular sieve using Fe, Cu, P, etc., so as to improve the alkali nitrogen resistance of the cracking catalyst, obtain a higher conversion rate, and obtain a lower gasoline olefin content, a higher liquefied gas yield, a higher diesel yield or a higher gasoline yield. Summary of the invention
[0011] One of the purposes of the present invention is to provide a method for modifying a catalytic cracking catalyst, which utilizes a nitrogen-capturing active component to selectively adsorb nitrogen-containing compounds in a catalytic cracking feedstock, thereby inhibiting the poisoning effect of nitrogen-containing compounds on common molecular sieves used for hydrocarbon cracking, and allowing hydrocarbon molecules and nitrogen-containing compound molecules in heavy oil to "react separately", thereby improving the catalytic cracking catalyst's ability to resist alkali nitrogen poisoning.
[0012] Another object of the present invention is to promote the cracking and condensation dehydrogenation reaction of nitrogen-containing compounds on the surface of the nitrogen-capturing active component, so that they can be removed in the form of coke, thereby preventing the nitrogen-containing compounds from entering the target product, thereby reducing the adverse effects of the nitrogen-containing compounds on the properties of the target product and subsequent processing.
[0013] The technical problem to be solved by the present invention is to provide a modification and preparation method of a catalytic cracking catalyst resistant to alkaline nitrogen. The catalytic cracking catalyst is used in the catalytic cracking reaction process of a raw oil with a high content of alkaline nitrogen-containing compounds, and its alkaline nitrogen content is 300-3000 μg / g, and has a high conversion rate and a good product distribution.
[0014] The strong adsorption and preferential adsorption of nitrogen-containing compounds are the key factors causing catalyst poisoning. Therefore, a special nitrogen-capturing active material can be designed to have a strong adsorption capacity for nitrogen-containing compounds, and then this active material can be loaded on the surface of the catalyst carrier to adsorb nitrogen-containing compounds. In this way, the poisoning effect of nitrogen-containing compounds on ordinary molecular sieves used for hydrocarbon cracking can be avoided, and the hydrocarbon molecules and nitrogen-containing compound molecules in heavy oil can be "separately reacted". At the same time, this special active material can also promote the cracking reaction of nitrogen-containing compounds, especially the condensation dehydrogenation reaction. Through the transfer of hydrogen, the nitrogen-containing compounds are highly condensed. On the one hand, hydrogen is transferred to the target product, the utilization rate of hydrogen in the raw material is improved, and the product quality is improved. On the other hand, nitrogen is adsorbed on the catalyst and removed in the form of coke, which prevents nitrogen-containing compounds from entering the target product, thereby avoiding adverse effects on the properties and subsequent processing of the target product.
[0015] To achieve the above object, the present invention provides a catalytic cracking catalyst comprising the following components:
[0016]
[0017] Wherein, the nitrogen-capturing active component is metal zirconium oxide.
[0018] The catalytic cracking catalyst of the present invention, wherein the content of the nitrogen-trapping active component is 0.1 to 5 parts by weight.
[0019] The catalytic cracking catalyst of the present invention preferably contains 0.1 to 2 parts by weight of the nitrogen-trapping active component.
[0020] In the catalytic cracking catalyst of the present invention, the source of the metal zirconium oxide includes at least one of ZrO2, zirconium nitrate and zirconium silicate.
[0021] The catalytic cracking catalyst of the present invention, wherein the cracking active component is at least one of Y-type molecular sieve, HY-type molecular sieve, USY-type molecular sieve, REY-type molecular sieve, REHY-type molecular sieve and ZSM-5 molecular sieve.
[0022] The catalytic cracking catalyst of the present invention, wherein the clay is at least one of kaolin, diatomaceous earth, montmorillonite, hydrotalcite and bentonite.
[0023] The catalytic cracking catalyst of the present invention, wherein the binder is at least one of silica sol, alumina sol and pseudo-boehmite.
[0024] The present invention also provides a method for preparing the above catalytic cracking catalyst, comprising the following steps:
[0025] (1) using conventional methods in the art to prepare a catalyst intermediate from a cracking active component, clay and a binder;
[0026] (2) The nitrogen-trapping active component is prepared as an aqueous solution and directly impregnated onto the catalyst intermediate obtained in step (1), followed by drying and calcining.
[0027] The preparation method of the catalytic cracking catalyst of the present invention comprises the following steps: the nitrogen-trapping active component is zirconium nitrate; the drying condition is 110-250° C. in an air atmosphere for 1-5 hours, preferably 120° C. for 2 hours; the calcination condition is 500-700° C. in an air atmosphere for 0.5-3 hours, preferably 550° C. for 2 hours.
[0028] The present invention further provides a method for preparing the catalytic cracking catalyst, which comprises: mixing and slurrying the nitrogen-capturing active component, the cracking active component, clay and a binder, and spray-drying and forming the mixture.
[0029] The preparation method of the catalytic cracking catalyst of the present invention comprises the following conditions: the mixing and slurrying are performed at room temperature, the solid content is 10 to 40 parts by weight, the pH value is 1.8 to 5.2, the stirring rate is 30 to 600 r / min, and the spray drying molding is performed under the condition that the hot air temperature is controlled at 550 to 700°C.
[0030] The present invention further provides a method for preparing the above catalytic cracking catalyst, comprising the following steps:
[0031] (1) mixing nitrogen-capturing active components, clay and a binder, slurrying, spray drying and molding to obtain a catalyst intermediate;
[0032] (2) Mixing the cracking active component with the catalyst intermediate obtained in step (1), slurrying, spray drying and forming.
[0033] The preparation method of the catalytic cracking catalyst of the present invention, wherein the mixing and beating conditions in step (1) are at room temperature, a solid content of 10 to 40 parts by weight, a pH value of 5.0 to 7.0, and a stirring speed of 30 to 600 r / min; the spray drying and molding conditions are that the hot air temperature is controlled at 550 to 700°C; the mixing and beating conditions in step (2) are at room temperature, a solid content of 10 to 40 parts by weight, a pH value of 1.8 to 5.2, and a stirring speed of 30 to 600 r / min; the spray drying and molding conditions are that the hot air temperature is controlled at 550 to 700°C.
[0034] The present invention can also be described in detail as follows:
[0035] The present invention provides a modification and preparation method for improving the ability of a catalytic cracking catalyst to resist alkali nitrogen poisoning. The catalytic cracking catalyst contains 0.1 to 5% by weight of a nitrogen-trapping active component, 10 to 50% by weight of a cracking active component, 10 to 80% by weight of clay and 10 to 30% by weight of a binder, wherein the nitrogen-trapping active component is an oxide of metal zirconium, and its content is 0.1 to 5% by weight in terms of ZrO2.
[0036] The nitrogen-capturing active component described in the present invention is metal zirconium oxide, and its preferred content is 0.1 to 2% by weight calculated as ZrO2.
[0037] The cracking active component described in the present invention is a commonly used active component of catalytic cracking catalysts well known to those skilled in the art, for example, it can be one or more of Y-type molecular sieve, HY-type molecular sieve, USY-type molecular sieve, REY-type molecular sieve, REHY-type molecular sieve, and ZSM-5 molecular sieve.
[0038] The clay described in the present invention is clay commonly used in catalytic cracking catalysts well known to those skilled in the art, for example, it may be one or more of kaolin, diatomaceous earth, montmorillonite, hydrotalcite, and bentonite.
[0039] The binder described in the present invention is a binder commonly used in catalytic cracking catalysts well known to those skilled in the art, for example, it can be one or more of silica sol, alumina sol and pseudo-boehmite.
[0040] The nitrogen-capturing active component described in the present invention is added in the following form:
[0041] (1) Powder of ZrO2, zirconium nitrate, zirconium silicate or one or more of them is mixed with other components of catalytic cracking catalyst, including molecular sieve, matrix, binder, etc., and then slurried, spray-dried and molded.
[0042] (2) Powder of ZrO2, zirconium nitrate, zirconium silicate or one or more thereof is mixed with a matrix of a catalytic cracking catalyst and a binder, and then slurried and roasted to prepare a catalytic cracking catalyst carrier material containing ZrO2, and then mixed with an active component, slurried, spray-dried, and formed.
[0043] (3) The aqueous solution of zirconium nitrate is directly impregnated onto the formed catalytic cracking catalyst, and then dried and calcined.
[0044] The preferred addition form of the nitrogen-capturing active component in the present invention is to directly impregnate the aqueous solution of zirconium nitrate onto the formed catalytic cracking catalyst, followed by drying and calcining.
[0045] The main innovative features of the present invention are:
[0046] ① The catalytic cracking catalyst contains 0.1-5 wt% of nitrogen-capturing active component, 10-50 wt% of cracking active component, 10-80 wt% of clay and 10-30 wt% of binder, wherein the nitrogen-capturing active component is metal zirconium oxide, and its content is 0.1-5 wt% calculated as ZrO2, and preferably 0.1-2 wt% calculated as ZrO2.
[0047] ② The nitrogen-capturing active component described in the present invention is added in the following form:
[0048] (1) Powder of ZrO2, zirconium nitrate, zirconium silicate or one or more of them is mixed with other components of catalytic cracking catalyst, including molecular sieve, matrix, binder, etc., and then slurried, spray-dried and molded.
[0049] (2) Powder of ZrO2, zirconium nitrate, zirconium silicate or one or more thereof is mixed with a matrix of a catalytic cracking catalyst and a binder, and then slurried and roasted to prepare a catalytic cracking catalyst carrier material containing ZrO2, and then mixed with an active component, slurried, spray-dried, and formed.
[0050] (3) The aqueous solution of zirconium nitrate is directly impregnated onto the formed catalytic cracking catalyst, and then dried and calcined.
[0051] The preferred addition form of the nitrogen-capturing active component in the present invention is to directly impregnate the aqueous solution of zirconium nitrate onto the formed catalytic cracking catalyst, followed by drying and calcining.
[0052] Beneficial effects of the present invention:
[0053] Compared with the prior art, the method provided by the present invention has the following advantages:
[0054] (1) Compared with unmodified catalysts, catalysts with added nitrogen-capturing active components can inhibit the poisoning effect of nitrogen-containing compounds on ordinary molecular sieves used for hydrocarbon cracking, allowing hydrocarbon molecules and nitrogen-containing compound molecules in heavy oil to "react separately", thereby improving the catalytic cracking catalyst's resistance to alkali nitrogen poisoning.
[0055] (2) Compared with unmodified catalysts, it can improve the conversion rate of high nitrogen-containing heavy oil and increase the yield and selectivity of gasoline and diesel.
[0056] (3) Compared with the unmodified catalyst, the nitrogen content in the coke can be increased, thereby reducing the nitrogen content in target products such as gasoline and diesel, which is beneficial to the subsequent refining process of light oil products. DETAILED DESCRIPTION
[0057] The preferred embodiments are listed below to explain the present invention in detail. Although the following embodiments are implemented on the premise of the technical solution provided by the present invention and provide detailed implementation methods and processes, the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.
[0058] Example 1
[0059] This example is used to illustrate the catalytic cracking catalyst provided by the present invention.
[0060] (1) Preparation of blank catalyst: Y-type molecular sieve, kaolin, pseudo-boehmite and hydrochloric acid were used as raw materials. The total amount of Y-type molecular sieve (mass fraction was 30%) and the mass ratio of kaolin and alumina were kept unchanged. They were mixed and slurried, dried, calcined, and sieved to obtain particles of 80-180 mesh. The particles were then aged at 800°C and 100% steam for 4 h to obtain a blank catalyst without metal modification, which was marked as Cat-A.
[0061] (2) Preparation of Zr-modified kaolin: Dissolve zirconium nitrate (molecular formula: Zr(NO3)4·5H2O) in distilled water, and use the incipient wetness method to impregnate the ground kaolin with the zirconium nitrate solution in multiple times, dry at 120°C for 2 hours, and then calcine at 550°C for 2 hours to obtain the Zr-modified kaolin component.
[0062] Preparation of Zr-modified catalyst: The corresponding Zr-free kaolin component was replaced by the above-mentioned Zr-modified kaolin component, and the same preparation method as the blank catalyst was adopted to obtain a Zr-modified kaolin catalyst, marked as Cat-B, in which the ZrO2 content was 1 weight%.
[0063] Example 2
[0064] The catalyst obtained by directly adding zirconium nitrate (molecular formula: Zr(NO3)4·5H2O) during the catalyst gelling process is marked as Cat-C, in which the content of ZrO2 is 1% by weight.
[0065] Example 3
[0066] A certain amount of zirconium nitrate aqueous solution was directly impregnated on the prepared catalyst Cat-A, and then after drying, calcination and aging treatment, the catalyst Cat-D was obtained, in which the content of ZrO2 was 1% by weight.
[0067] Example 4
[0068] A certain amount of zirconium nitrate aqueous solution was directly impregnated on the prepared catalyst Cat-A, and then the catalyst Cat-E was obtained after drying, calcination and aging treatment, in which the content of ZrO2 was 2% by weight.
[0069] Comparative Example 1
[0070] Preparation of unmodified catalyst: Y-type molecular sieve, kaolin, pseudo-boehmite and hydrochloric acid are used as raw materials, the total amount of Y-type molecular sieve (mass fraction is 30%) and the mass ratio of kaolin and alumina are kept unchanged, they are mixed and slurried, dried, roasted, and sieved to obtain particles of 80-180 mesh, and then aged at 800°C and 100% water vapor for 4 hours to obtain a blank catalyst without metal modification, marked as Cat-A.
[0071] Test Example 1
[0072] The catalysts prepared in the above examples were aged for 4 hours at 800°C and 100% steam before use. The catalytic cracking reaction experiments were all completed on a fixed bed microreactor experimental device, which was designed in accordance with the standard of ASTM D3907-80 of the United States, including a microcomputer control part, a feed part, a heating furnace and a reactor part, a product condensation recovery and metering system, etc. The raw material used was Shengli coking wax oil, and its properties are shown in Table 1. The oil intake for each evaluation experiment was about 1g, the catalyst loading was 6g, the reaction temperature was 515°C, and the product distribution after the reaction was shown in Table 2.
[0073] Table 1 Properties of Shengli coking wax oil
[0074]
[0075]
[0076] Table 2 Effect of Zr modification on catalyst reaction performance
[0077]
[0078] It can be seen from the above reaction results that, compared with the unmodified catalyst, the catalyst with the addition of nitrogen-trapping active components using the catalytic cracking catalyst of the present invention can inhibit the poisoning effect of nitrogen-containing compounds on ordinary molecular sieves used for hydrocarbon cracking, so that the hydrocarbon molecules and nitrogen-containing compound molecules in the heavy oil "react separately", thereby improving the catalytic cracking catalyst's resistance to alkali nitrogen poisoning, thereby improving the conversion rate of nitrogen-containing heavy oil, and significantly increasing the content of nitrogen in the coke, thereby reducing the nitrogen content in the target product.
Claims
1. A catalytic cracking catalyst for use in a catalytic cracking reaction of a feedstock oil having a high content of basic nitrogen-containing compounds, wherein the sum of the contents of the components in the catalyst is 100% by weight, and the catalyst comprises the following components: Nitrogen capture active component 0.1~5% by weight; Cracking active component 10~50% by weight; Clay 10~80% by weight; Binder 10~30% by weight; in, The nitrogen-capturing active component is an oxide of metal zirconium, and its content is calculated as ZrO2; The cracking active component is at least one of a Y-type molecular sieve and a ZSM-5 molecular sieve, and the Y-type molecular sieve is at least one of a HY-type molecular sieve, a USY-type molecular sieve, a REY-type molecular sieve, and a REHY-type molecular sieve.
2. The use according to claim 1, characterized in that: The content of the nitrogen-capturing active component is 0.1-2% by weight, calculated as ZrO2.
3. The use according to claim 1, characterized in that: The clay is at least one of kaolin, diatomaceous earth, montmorillonite, hydrotalcite and bentonite.
4. The use according to claim 1, characterized in that: The binder is at least one of silica sol, alumina sol and pseudo-boehmite.
5. The use according to claim 1, characterized in that: The preparation method of the catalyst comprises the following steps: (1) preparing a catalyst intermediate from a cracking active component, clay and a binder; (2) Directly impregnate the catalyst intermediate obtained in step (1) with an aqueous solution of zirconium nitrate, and then dry and calcine.
6. The use according to claim 5, characterized in that: The drying condition is 110-250° C. in an air atmosphere for 1-5 hours; the calcination condition is 500-700° C. in an air atmosphere for 0.5-3 hours.
7. The use according to claim 6, characterized in that: The drying condition is 120° C. and drying for 2 hours.
8. The use according to claim 6, characterized in that: The calcination condition is 550° C. for 2 hours.
9. The use according to claim 1, characterized in that: The preparation method of the catalyst comprises the following steps: mixing and slurrying ZrO2 powder, one or more zirconium nitrate and zirconium silicate, cracking active components, clay and a binder, and spray drying and forming the mixture.
10. The use according to claim 9, characterized in that: The mixing and beating conditions are room temperature, pH value 1.8-5.2, and stirring rate 30-600 r / min; the spray drying molding conditions are hot air temperature controlled at 550-700°C.
11. The use according to claim 1, characterized in that: The preparation method of the catalyst comprises the following steps: (1) mixing ZrO2 powder, one or more of zirconium nitrate and zirconium silicate, clay and a binder, beating the mixture, and spray drying the mixture to obtain a catalyst intermediate; (2) The cracking active component is mixed with the catalyst intermediate obtained in step (1), slurried, and spray-dried to form a shape.
12. The use according to claim 11, characterized in that: The mixing and beating conditions in step (1) are at room temperature, pH value 5.0-7.0, and stirring speed 30-600 r / min; the spray drying molding conditions are that the hot air temperature is controlled at 550-700°C; The mixing and beating conditions in step (2) are room temperature, pH value 1.8-5.2, and stirring rate 30-600 r / min; the spray drying molding conditions are hot air temperature controlled at 550-700°C.
Citation Information
Patent Citations
Anti-basic nitrogen olefin reduction cracking catalyst and preparation method thereof
CN103084199A
Anti-basic nitrogen catalysis cracking catalyst and preparation method thereof
CN103084200A
Anti-basic nitrogen liquefied gas yield increase cracking catalyst and preparation method thereof
CN103084205A
Anti-basic nitrogen diesel oil yield increase catalysis cracking catalyst and preparation method thereof
CN103084206A
Anti-basic nitrogen gasoline yield increase catalysis cracking catalyst and preparation method thereof
CN103084207A
